Barriers and facilitators to cognitive impairment screening among older adults with diabetes mellitus and hypertension by primary healthcare providers in rural Uganda - Muwanguzi, Moses; Obua, Celestino; Maling, Samuel; Wong, Wilson; Owokuhaisa, Judith; Wakida, Edith K. (Frontiers in Health Services, 2023)
Background: The burden of non-communicable diseases and cognitive impairment exhibit a linear rise in sub-Saharan Africa due to the increase in life expectancy. Non-communicable diseases like diabetes mellitus and hypertension increase the risk for cognitive impairment. To improve our understanding of the underpinnings of cognitive impairment screening, this study explored the barriers and facilitators of routine cognitive impairment screening in a primary healthcare setting guided by the Capacity, Opportunity, Motivation Behavioral change (COM-B) model. Methods: This was a descriptive qualitative study with primary healthcare providers who provide care to older adults with diabetes mellitus and hypertension at three primary healthcare centres in Mbarara district southwestern Uganda. In-depth interviews were conducted using a semi structured interview guide. Interviews were audio-recorded, transcribed verbatim, and analyzed using the framework approach along the COM-B components. For each COM-B component, factors were categorized as barriers and facilitators. Results: We conducted 20 in-depth interviews with clinical officers, enrolled nurses, and a psychiatric nurse. The questions were guided by the Capacity, Opportunity and Motivation Behavioral change (COM-B) framework to identify barriers and facilitators to cognitive impairment screening. The factors that negatively affected the screening were considered as barriers, while the positive ones as facilitators. Capacity related barriers to cognitive impairment screening included chronic understaffing, primary healthcare provider non-involvement, lack of training/skills, lack of knowledge and awareness in screening, absence of caretakers, lack of patient awareness of cognitive problems; while facilitators were staff recruitment, primary healthcare provider involvement, and specialized training. Opportunity related barriers to screening included patient overload, infrastructure shortage, and time constraints. Motivation related barriers included lack of screening guidance and policy, while the facilitators were availability of mentorship programs for primary healthcare providers. Conclusions: Integrating cognitive impairment screening in primary health care requires engagement of relevant stakeholders with the focus on addressing implementation challenges through capacity development. Timely cognitive impairment screening at the first point of care initiates a cascade of interventions for timely enrollment into care, thus arresting the progress of cognitive impairment that leads to dementia.